Analysis Of The Effect Of Health Promotion With Poster Media About Tooth Loos On Importsnt Knowledge Of Using Dentures In People Aged 40-60 Years In Sumurgung Village, Tuban - Tri Yogi Yohanita (Universitas STRADA Indonesia, 2023)
Changes that occur due to tooth loss have an impact on a decrease in masticatory efficiency which indirectly affects a person's general health. Loss of teeth can also have an emotional and functional impact and can affect aesthetics. Another consequence is that it can affect the appearance and emotions of most people. Treatment with the use of dentures as a replacement for areas that have lost teeth is very important, but not everyone who has lost teeth uses dentures. This study is a quantitative study using a quasi-experimental design with a pre-test post-test control group. implemented as a measure of intervention. The subject of this research is the Sumurgung village community with 30 respondents, the data analysis uses the Wilcoxon test and the Mann Whitney test. The results of the analysis obtained a significant difference from the test results between the experimental group and the control group against the Sumurgung Tuban village community group regarding tooth loss on the importance of using cellphones at the age of 40-60 years which in the group p value 0.002 < (0.05) and dirty group with p value 0.257 > (0.05). And the statistic of Mann test-significance p 0.000 < 0.05. This shows that there is a significant difference between the intervention group and the control group. The difference between the control group and the intervention group has an important meaning, namely the promotion of dental health using the Effective Poster media to increase knowledge about the importance of using early 40-60 year olds in Sumurgung Village, Tuban.